After genocide: bringing the devil to justice - Smith, Adam M. (Prometheus Books, 2009)
From Budapest to Bondi to Bosnia : an unlikely war crimes journey -- An odd, misguided debate : is it really international justice or no justice? -- Left behind -- The politics of hell : what happened? -- International justice from the ground up : falling on deaf ears (Part I): who do international courts prosecute? -- Falling on deaf ears (part II) : "unfair and unhelpful" -- The International Criminal Court and the limits of international justice -- They say it can't be done -- Croatia : justice in the shadow of the Hague -- Conclusion : is it too late to listen to the canary in the mine?